The great radio sitcoms - Cox, Jim 1939- (McFarland, 2007)
"This volume examines 20 of the most popular sitcoms which aired between the mid-1920s and early 1950s during the three decade heyday of radio. Each series is discussed from an artistic standpoint, taking a look at the program's character development and extent of vaudeville heritage"--Provided by publisher